2020
DOI: 10.3390/molecules25215007
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Insights into Human Transmembrane Protease Serine-2 (TMPS2) Inhibitors against SARS-CoV2: Homology Modelling, Molecular Dynamics, and Docking Studies

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV2), which caused novel corona virus disease-2019 (COVID-19) pandemic, necessitated a global demand for studies related to genes and enzymes of SARS-CoV2. SARS-CoV2 infection depends on the host cell Angiotensin-Converting Enzyme-2 (ACE2) and Transmembrane Serine Protease-2 (TMPRSS2), where the virus uses ACE2 for entry and TMPRSS2 for S protein priming. The TMPRSS2 gene encodes a Transmembrane Protease Serine-2 protein (TMPS2) that belongs to the ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…It was discovered that GBPA, the active metabolite of camostat mesilate, inhibits TMPRSS2 and prevents SARS-CoV-2 infection of human airway cells. [6][7][8][9][10][11][12][13] Furthermore, a smallscale retrospective study suggested a potential therapeutic effect of camostat mesilate in patients admitted to an intensive care unit. 21 Despite promising results of preclinical studies, as well as a small retrospective study, the results of our study indicate that camostat mesilate is no more effective than placebo for treating patients with mild to moderate SARS-CoV-2 infection with or without symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was discovered that GBPA, the active metabolite of camostat mesilate, inhibits TMPRSS2 and prevents SARS-CoV-2 infection of human airway cells. [6][7][8][9][10][11][12][13] Furthermore, a smallscale retrospective study suggested a potential therapeutic effect of camostat mesilate in patients admitted to an intensive care unit. 21 Despite promising results of preclinical studies, as well as a small retrospective study, the results of our study indicate that camostat mesilate is no more effective than placebo for treating patients with mild to moderate SARS-CoV-2 infection with or without symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro drug-screening studies have indicated that 4-(4-guanidinobenzoyloxy)phenylacetic acid (GBPA), the active metabolite of the serine protease inhibitor camostat mesilate (FOY-305), inhibits TMPRSS2 and prevents SARS-CoV-2 infection of a human airway epithelial cell-derived cell line (Calu-3 cells). 613…”
Section: Introductionmentioning
confidence: 99%
“…The 3D structure of TMPRSS2 was obtained from Brookhaven protein databank (PDB ID: 7 MEQ) [ 12 ]. The TMPRSS2 FASTA sequence (accession number: O15393) was extracted from the UniProt database and modelled with Swiss model server using the crystal structure (PDB ID: 7MEQ) as a template because of the presence of some missing loop regions in the resolved crystal structure [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Kishk et al identified proteins with known X-ray structure and high homology for TMPRSS2 using SWISS-MODEL and NCBI blastp [ 102 ]. These proteins included transmembrane protease serine 1 and 13 and a group of human plasma kallikrein.…”
Section: Molecular Modeling Studiesmentioning
confidence: 99%